BRAND COMMUNICATION END THE CHILDREN´S AUDIENCE: the influence of advertisements end marketing actions in the daily lives of children end adolescentes - Santos Parreira, Brenda dos; Nogueira, Bruna Maria; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
If commercial brands become known as early as possible, they can stand out from competitors and have more opportunities to be remembered from childhood to adulthood. In this way, this study seeks to assess the impact of brand communications on the daily lives of children and adolescents, examining whether advertisements and other marketing actions influence the choices of these young people and potential consumers. For this, the study theoretically assesses the difficulties of preventing children and adolescents from being exposed to numerous advertisements, because even with certain regulations, they remain connected to the Internet for a long time, often without the proper monitoring of parents or guardians. Then, in order to verify the problem in practice, it presents a quantitative survey, in which 100 children and adolescents answer questions about their consumption habits and the influence of brands. What can be seen from this study is that this exposure, so early to brands, has a direct influence on the habits and choices of these young people, and can be harmful in many cases, given the huge amount of offers and content of the most varied types that reach them every day, especially through the online universe.
Keywords: Brand communication; Media exhibition; Teens